As cartas rufinianas: um diálogo inconcluso - Jesus, Flora de (2014)
This dissertation attempts to describe the way Joel Rufino dos Santos makes literature in the work When I returned, I had a surprise ( letters to Nelson) (2000), the autobiographical content, composed of letters written when political prisoner in the Racecourse prison in the city of São Paulo, which had as the main addressee his son Nelson. It is intended, putting it in dialogue, first, with the work of the same author, also autobiographical, That’s the way it was (if it seems to me) (2008a), to reflect about "how" the author-creator deals with certain themes of Brazilian society. Among the themes, the condition of black people and their place in the society, the function the football art had in Brazil, the relationship between literature and history, the intellectual response faced with needs of people, his reflections as a political prisoner, the role of literature related to these issues, all of them alluded in the letters, even if in a pedagogical-juvenile way. It was chosen an interpretive methodology of qualitative nature and, from the idea that language, especially literary, is composed of the interaction with the other say , permeated by religious, ethical , aesthetic and social values, built within a certain culture. It is assumed here, based on this thought, that the author-creator, in his letters, appropriates sayings already said, romanticized or not, with the intention to empower their voices, links of his own voice, demystifying consolidated knowledge and trying to (re) establish not designed places in a society built on European conceptual pillars. This proposed analysis insists on not losing sight of the context of Brazilian society in process - before, during and after the writing of the letters - contemplating the act of writing and reading in the act of living, and the building of proclaimed voices among the contingencies and ambivalences of the deafened scream for freedom in modern times.